Evaluating Cooperative Membership’s Impact on Rural Household Empowerment: A Mixed-Methods Study in Nangarhar Province, Afghanistan - Rahimi, Mohammad Rahim (Journal of Economics and Business UBS, 2025)
Rural cooperatives are widely promoted as vehicles for socio-economic development and empowerment in low-income contexts. However, empirical evidence on their effectiveness in fragile, conflict-affected settings remains scarce. This study fills that gap by assessing how membership in agricultural cooperatives influences multiple dimensions of household empowerment in Nangarhar Province, Afghanistan. Employing a convergent mixed-methods design, we surveyed 420 households (210 cooperative members; 210 matched non-members) using propensity score matching (PSM) and conducted 24 in-depth interviews. Quantitative data were analyzed to estimate the average treatment effect on the treated (ATT), while qualitative transcripts were coded thematically in NVivo. Cooperative membership yields a significant 17.4 percentage-point increase in women’s participation in farm decision-making and a 12.8-point rise in access to microcredit (p < .05). Qualitative insights reveal that social capital building, peer mentoring, and collective bargaining explain these gains. Findings demonstrate that cooperatives can serve as effective empowerment mechanisms even in unstable regions. The cross-sectional design limits causal inference beyond ATT estimates; future research should implement longitudinal or experimental approaches to track dynamic empowerment trajectories.